2015
DOI: 10.1111/aogs.12642
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged pegylated liposomal doxorubicin treatment for recurrent pelvic cancers: a feasibility study

Abstract: We conducted a proof of concept study evaluating prolonged treatment with pegylated liposomal doxorubicin for recurrent ovarian, tubal and peritoneal carcinoma. Thirteen consecutive patients received an average of 22.6 cycles of pegylated liposomal doxorubicin, with an average cumulative dose of 1409 mg/m(2) . Progression-free survival at 18 months was 61.5%, and was longer than the previous progression-free survival in 10 of the 13 patients. Overall 5-year survival was 78.8%. Despite prolonged use and relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…There are multiple case series reporting outcomes for over 100 patients undergoing treatment with prolonged courses of PLD (>450 mg/m 2 ). In these case series, there were no patients with any clinical evidence of cardiac toxicity, and only one reported to have >10% change in ejection fraction without any symptoms of heart failure (Rabinovich et al, 2015; Safra et al, 2000; Uyar et al, 2004; Gill et al, 2013; Kesterson et al, 2010). Our data on an additional 18 women with cumulative PLD doses ranging from 660 mg–2794 mg and no symptoms of cardiotoxicity, support these findings.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…There are multiple case series reporting outcomes for over 100 patients undergoing treatment with prolonged courses of PLD (>450 mg/m 2 ). In these case series, there were no patients with any clinical evidence of cardiac toxicity, and only one reported to have >10% change in ejection fraction without any symptoms of heart failure (Rabinovich et al, 2015; Safra et al, 2000; Uyar et al, 2004; Gill et al, 2013; Kesterson et al, 2010). Our data on an additional 18 women with cumulative PLD doses ranging from 660 mg–2794 mg and no symptoms of cardiotoxicity, support these findings.…”
Section: Discussionmentioning
confidence: 87%
“…The literature, another source of guidance for prescribing physicians, describes a much less significant level of cardiac risk. There are several reports of small numbers of patients who received more than the 500 mg/m 2 of PLD with no significant cardiac ramifications (Blank et al, 2017; Grenader et al, 2010; Rabinovich et al, 2015; Safra et al, 2000; Uyar et al, 2004). There are additional reports indicating routine monitoring is futile due to high level of safety of even prolonged courses of PLD (Gill et al, 2013; Kesterson et al, 2010; Skubitz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 509 women with metastatic breast cancer, cardiac toxicity (defined by declining LVEF) during treatment and follow up was less frequently associated with pegylated liposomal doxorubicin than with conventional doxorubicin; cardiotoxicity developed in 4% versus 19% of cases, cardiotoxicity with signs and symptoms of CHF in 0% versus 4% of cases, and cardiotoxicity without signs and symptoms of CHF in 4% versus 15% of cases, respectively [7]. Several trials and case reports of breast and gynecological cancer have shown that patients treated with pegylated liposomal doxorubicin showed no signs or symptoms of CHF, even when they received a cumulative dose of pegylated liposomal doxorubicin > 1000 mg/m 2 [1721]. In contrast, 0–5% of patients experienced a reduction in LVEF of ≥20% relative to baseline [1720].…”
Section: Discussionmentioning
confidence: 99%
“…liposomes (nano-sized lamellar phase) already on the market for the delivery of a range of drugs (Kaminskas et al, 2012;Negrini et al, 2015;Rabinovich et al, 2015), and for slow release injections (Haasen et al, 2017). The dispersed mesophases (comprising nano-sized mesophase particles) are often preferred over the bulk phase as the bulk phases are generally highly viscous (especially in the case of bicontinuous cubic V 2 phase) and difficult to handle (Larsson, 1999).…”
Section: Mesophase Structure Formation During Digestion In Pharmaceutical Applicationsmentioning
confidence: 99%